Sensitivity of composite scarf joints to manufacturing deviation and disbond under tensile load - Larkin, David J.; Giannopoulos, Ioannis K.; Theotokoglou, Efstathios E. (Cranfield University, 2017)
Scarf joints are an effective method of bonding thick composite laminates for applications such as the repair of composite aircraft structures. However, concerns remain about their damage tolerance characteristics. Typically composite scarf repairs to aircraft structures require use of hand tools or rudimentary jigs. If the scarf is incorrectly prepared, this may cause a profile deviation to the joint, affecting the bond line stresses and in turn, reducing the residual strength of the joint or repair. The subject of this work examined the sensitivity of composite scarf joints to machining profile deviation and artificial disbond, when subject to static tensile load. Tensile test specimens were prepared with two different configurations of scarf for representing an undercut or imprecise scarf typical of a machining error. In addition, sensitivity of the scarf joints in the presence of an artificial disbond was also tested. Results indicated that for the specimens tested, the scarf is relatively insensitive to minor profile deviation, but highly sensitive to an artificial disbond. Experimental results were also compared with finite element analysis.